Deep Learning Algorithms and Their Applications - Turayeva Makhliyo Shokir qizi (Research Parks Publishing LLC, 2021)
The objective of this paper is to summarize a comparative account of unsupervised and supervised deep learning models and their applications. The design of a model system requires careful attention to the following issues: definition of pattern classes, sensing environment, pattern representation, feature extraction and selection, cluster analysis, classifier design and learning, selection of training and test samples and performance evaluation.